ANALISIS PERSEPSI SISWA KELAS X PADA PEMBELAJARAN LINTAS MINAT BIOLOGI PROGRAM PEMINATAN ILMU – ILMU SOSIAL (IIS) SE-KOTA PEKANBARU - Eka Sari Ninsih; Wan Syafi’i; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine students' perceptions of class X on learning across Biology interest program of Social Sciences in Pekanbaru City. This is a descriptive research using survey method conducted in April until June 2018. The population in this study is the X class students of biology interest program which amounted to 326 students, consisting of 5 schools, they are SMAN 1, SMAN 4, SMAN 5, SMAN 8 and SMAN 12 Pekanbaru. The sample in this study amounted to 180 students determined based on random technique. Instruments used for data collection in the form of questionnaire instruments and interviews. The result of the research shows that the perception of the students of class X on learning cross-interest in Biology program of Social Sciences in Pekanbaru City is 74% which is good, with perception indicator that is 70% absorption which is enough, equal to 71% which is good, and indicator of rating equal to 81% which is good. Overall the perception of the students of class X on learning cross-interest in Biology program of Social Sciences in Pekanbaru City is 74% which is good. Opening of cross-interest program at school, not in accordance with the demands of Curriculum 2013. Implementation of practicum in learning cross-interest Biology has not fulfilled the criteria of Curriculum demand 2013.Keywords: Perception, cross biological interest, Social Sciences Program